ANALISIS EFEKTIVITAS IKLAN-IKLAN TV BERTEMA LOCAL CONTENT DI INDONESIA TAHUN 2004 - Maer, Bernadette Dian Arini; Tanudjaja, Bing Bedjo; Banindro, Baskoro Suryo (Institute of Research and Community Outreach - Petra Christian University, 2007)
In the globalization era, local content TV commercials are considered to be more and more important. This thesis aims to analyze how far the local content TV commercials can be accepted by the Indonesian audience, who are culturally diverse; moreover, this thesis would analyze how these commercials contribute positively to the advertisers. Abstract in Bahasa Indoensia: Dalam era globalisasi, iklan bertema local content semakin dianggap penting. Karya tulis ini menganalisis sejauh mana iklan televisi bertema local content dapat diterima oleh masyarakat Indonesia yang memiliki kemajemukan budaya tinggi, serta memberikan kontribusi bagi pengiklan. Kata kunci: Efektivitas, iklan televisi, local content, Indonesia